St John's Wort Complementary Therapy for ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
A randomized, double-blind, placebo-controlled trial of hypericum perforatum (St John's Wort) in the treatment of attention-deficit/hyperactivity disorder (ADHD) was conducted in 54 children aged 6 to 17 years at Bastyr University, Kenmore, WA.